2018
DOI: 10.1308/rcsbull.2018.296
|View full text |Cite
|
Sign up to set email alerts
|

Computed tomography in the assessment of the acute abdomen

Abstract: Current limitations in service provision and potential future solutions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…Urinary tract stones were the most common finding (57.8% of abnormal CT findings), while the rest had other conditions. They and other studies have also found that a good clinical evaluation is primary in guiding management, diagnostic choices, and therapeutic decisions (Nachiappan et al, 2018;Sconfienza, 2015).…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…Urinary tract stones were the most common finding (57.8% of abnormal CT findings), while the rest had other conditions. They and other studies have also found that a good clinical evaluation is primary in guiding management, diagnostic choices, and therapeutic decisions (Nachiappan et al, 2018;Sconfienza, 2015).…”
Section: Introductionmentioning
confidence: 92%
“…Timely identification of critical life-threatening causes remains a challenge. Computerized tomography (CT) helps examine patients with an acute abdomen to identify abdominal and pelvic organ pathologies (Master et al, 2005), making CT scan the primary technique for the diagnosis of acute abdominal pain because it is more accurate and informative (Nachiappan et al, 2018;Stoker et al, 2009).…”
Section: Introductionmentioning
confidence: 99%